The Wallonian view on the conceptions about six-years-old children: a dialogue with first grade teachers - Monteiro, Shirlei Nadaluti (Pontifícia Universidade Católica de São Paulo, 2021)
This article aims to present the findings of a master’s research that investigated what conception of a six-years-old child bases the performance of teachers who work in the 1st year of the Elementary School and how such conception interferes with their pedagogical practices, as well as presenting an education proposal for these teachers. To give theoretical support, Henri Wallon’s theory of development was used, which understands the human being in a complete and integrated way. The research had a qualitative approach and for the production of information, interviews were carried out with teachers who work in the 1st year of Elementary School in a school unit of the municipal network of the city of São Paulo, in order to identify in their speech what they think about the six-year-old child and work situations and / or proposals that take into account the characteristics of children in this age group are implemented. This research revealed that although teachers know the characteristics of the six-year-old child and the importance of playing for their development, they do not provide opportunities for this play to happen and understand playing only as an instrument for learning content and not as a possibility for development child.